Asuhan Kebidanan Berkelanjutan (Continuity of Care) pada Ny. W Umur 24 Tahun G1P0A0 - Nor Khalimah; Nor Hidayati; Nuning Kusuma Dewi; Mei LIa Nindya Zulis W (Yayasan Literasi Sains Indonesia, 2025)
Continuous midwifery care, or continuity of care, is an important aspect of maternal and newborn health. This care introduces the provision of comprehensive care throughout the antenatal, intrapartum, and postpartum periods, to provide comfort, increase maternal satisfaction, reduce unnecessary interventions, and prevent complications. . The purpose of this study was to provide continuous care to Mrs. W, 24 years old G1P0A0 at the Kedung I Jepara Health Center. The research design used was descriptive and case study. The results showed that Mrs. W, 24 years old G1P0A0, had a physiological pregnancy. The labor process took place normally at 39+1 weeks of gestation, accompanied by monitoring of the postpartum period and the condition of the newborn which went well and without complications. The conclusion of comprehensive midwifery care showed that during pregnancy, Mrs. W experienced discomfort in the form of back pain which was intervened with the teachings of Effleurage massage. The labor process took place normally, and to reduce pain in the First Stage, a counter pressure massage technique was used which was also based on scientific evidence. During the postpartum period, breast care and oxytocin massage are applied to stimulate optimal breast milk production. Meanwhile, in newborn care, sterile gauze is used to help speed up the process of umbilical cord release, in accordance with the principles of evidence-based care.